The Effect of Small-Sided Games on The Development of Student Leadership and Motivation - Yugi Rahmanudin Lugaya; Amung Ma’mun; Yudy Hendrayana (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2020)
Leadership has been identified as an important life skill but less developed among young athletes. Therefore, the researcher aimed to examine the development of the leadership by taking a formal educational approach for giving experience to the sport captains. Giving a motivation is one of captain's important tasks that must be faced in regular physical education classes. A captain must implement strategies or ways to motivate students who are not motivated to get involved and also maintain the motivation of students who are already involved. In addition, captains often report that their leadership tasks are mostly organizational tasks. The main objective of this study was to find out the relationship between the small-sided games model intentionally structured and non-intentionally structured on students’ developments and to know which one is better for early adolescents (12 -15 years), in junior high school. The population of the study were 48 students of SMPN 1 Subang who took part in the extracurricular activities of the National Basketball Association. The Random Cluster Sample technique was used to select the samples. The samples were 20 students for the control group and 20 students for the experimental group. There were two instruments used, namely IMI (Intrinsic Motivation Inventory) and Leadership Instruments. The results showed that the value of the motivation of the experimental group (M = 68.7) was higher than the value of the motivation of the control group (M = 43.6). The results of the experimental group Leadership value (M = 73.1) also showed a higher value than the control group Leadership value (M = 34.2). The results of the research conclude that a structured small-sided games are effective in increasing the students’ leadership and motivation.